Seasonal variability of women's dietary diversity and food supply: a cohort study in rural Burkina Faso. Issue 9 (4th September 2022) - Lourme-Ruiz, Alissia; Koffi, Christophe Kouamé; Gautier, Denis; Bahya-Batinda, Dang; Bouquet, Emmanuelle; Dury, Sandrine; Martin-Prével, Yves; Savy, Mathilde
Abstract: Objective: To investigate the seasonal variations of women's dietary diversity (WDD) (items consumed and food supply) and its linkages with agriculture, market and wild resources. Design: A cohort of 300 women was followed-up over a year to investigate WDD and food sources (production, purchase or foraging). Monthly qualitative 24 h recalls allowed computing WDD Scores from a standard 10-food groups (FG) classification (WDDS-10). Associations between farm/women's characteristics and WDDS-10 were investigated using multivariate mixed models including interaction terms factor*months. Setting: Tuy province, Burkina Faso. Participants: 300 women of reproductive age. Results: Both dietary diversity and food sources were seasonal. The mean WDDS-10 was relatively stable from August to January (ranging from 3·1 to 3·5 FG) when farm production predominated. The WDDS-10 gradually increased from February, concomitantly with an increase in food purchases (onions, tomatoes, mangoes) and reached its highest levels (>4 FG) from March to June, when food purchases were still relatively high and when more women consumed foraged fruits (shea plums and wild grapes). Women living on farms owning > 3 plough oxen and different animal species had significantly higher WDDS-10 than others (+0·28 and +0·35 FG, respectively). Women who practiced off-farm activities also had higher WDDS-10 than those who did not (+0·21 FG, P < 0·05). Other factors, for example, the number of foraged edible species, provided advantages in terms of dietary diversity only during certain seasons (October – January, P for interaction < 0·01). Conclusions: Diversifying women's diets throughout the year requires complementary interventions aimed at diversifying production, promoting foraging and increasing income-generating activities to enable food purchasing.